LOOKING INTO THEME-RHEME STRUCTURE THROUGH DEMAND LETTERS AS COLLECTION INSTRUMENT (Proceedings of the International Conference on Education, 2019)
This research focused on demand letters, one of the most influential tools in business communication, on how they are written with the use of Systemic Functional Grammar of MAK Halliday. The purpose of this study is to understand and analyze these letters which are being manipulated in order to deliver the right context based on the needs of the writer. This paper studied three different types of Demand Letters, and identified the Theme and the Rheme of each of the sentences. Textual Analysis was employed in order to identify how the structure of demand letters deliver the subliminal messages embedded by the writers. Through Textual Analysis, the research is able unearth and foresee potential messages. It was found out that demand letters are often written using Unmarked-Marked Theme, which indicate that these letters are elaborately crafted in order to cater various meanings in just one sentence. The way in which writers develop their sentences can reveal their stance and intention. Additionally, it was discovered that most demand letters are written on a Derived Theme Progression which means that the initial sentence in the letter contains all the necessary information and succeeding sentences are just additional information. The letters appear to be written in which all the primary details were compacted in the first sentence primarily due to urgency and limitation of time. This study will be very beneficial to the academe as this becomes a proof that schools should start developing people to become more sensitive about unuttered messages through incorporating Functional Grammar to lessons such as Business Communication and Technical Writing.
Keywords: Demand Letters, Theme, Rheme, Functional Grammar